Exploring the Effect of Problem-Based Teaching and Learning Strategy on Students’ Learning Outcomes - Ajayi, Oreoluwa Senami; Oladele, Babatunde Kasim (Social Sciences and Education Research Review, 2024)
This study investigated the influence of problem-based teaching and learning technique on students' learning outcomes in economics in Lagos State. The study utilised a quasi-experimental design with a pretest, post-test, and control group. The design also included a 2x2 factorial matrix. A simple random technique was employed to choose six public schools within Lagos Education District II. The students were allocated to experimental and control groups using random assignments. The intact classrooms comprised 209 senior secondary I students, including 108 male and 101 female students. The instruments used were the Student's Attitude to Economics Scale (reliability coefficient of 0.88) and the Student's Economics Achievement Test (reliability coefficient of 0.77). The data were analysed using an analysis of covariance with a significance threshold of 0.05. The treatment had a substantial influence on students' learning outcomes (students' attitude to and achievement in economics, as indicated by the significant main effect (F (2,209) = 137.785, partial η2 = 0.51). The problem-based group of students achieved the highest average score of 80.97 in the learning outcomes, while the conventional group achieved an average score of 75.78. Gender did not have a notable impact on students' learning achievements. Furthermore, the statistical analysis revealed that the combined influence of treatment and gender did not yield a significant interaction effect. Implementing problem-based teaching and learning techniques led to enhanced learning outcomes in economics for senior secondary school students. Therefore, teachers are encouraged to employ this teaching and learning approach.